The Impact of Anti-Human Trafficking Laws on Local Communities in Cambodia: A Case Study of the Phnom Penh Region - Visal Nary Ponlok (Studies in Law and Justice, 2024)
This study examines the impact of Cambodia’s anti-human trafficking laws on local communities in the Phnom Penh region, focusing on both social and economic dimensions. The research highlights how these laws, while essential in combating human trafficking and providing legal protection to victims, have complex consequences for local livelihoods, employment, and community cohesion. It also explores the specific challenges faced by vulnerable populations, particularly women and children, in accessing protection services. Despite the intention to prevent trafficking and support victims, the enforcement of these laws often leads to unintended outcomes, such as economic disruption, social stigmatization, and gaps in service provision. The findings underscore the need for a more balanced approach that integrates robust law enforcement with sustainable support systems, community engagement, and tailored services to address the needs of affected populations effectively.